The science behind Superman's flight (Science Behind Superman, ,, 2017)
"Simple text describes real-world science of flight and how it compares to Superman's abilities"--
Soaring like Superman , Flying into the sky , Amazing animal flyers , Advanced flying machines.

The science behind Superman's sight (Science Behind Superman, ,, 2017)
"Simple text describes the real world science of sight and how it compares to Superman's abilities"--
Amazing eyes , Seeing the light , Improving vision , Going beyond our limits.

The science behind Superman's speed (Science Behind Superman, ,, 2017)
"Simple text describes the real-world science of speed and how it compares to Superman's abilities"--
Speed saves the day , Understanding speed , Fastest animals , Speediest vehicles.

The science behind Superman's strength (Science Behind Superman, ,, 2017)
"Simple text describes the real-world science of strength and how it compares to Superman's abilities"--
Super-strength , Strong muscles , Animal strength , Strength enhancements.